1996
DOI: 10.1002/(sici)1096-9071(199610)50:2<117::aid-jmv3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in South Africa: Evidence for sporadic spread and increased seroprevalence in rural areas

Abstract: Hepatitis E virus (HEV) is a major cause of non-A, non-B hepatitis in developing countries. Factors influencing sporadic spread of hepatitis E are unclear. We examined anti-HEV seroprevalence and demographic data from 407 urban and 360 rural black South African adults living in formal housing, squatter camps, or mud huts. Anti-HEV sero-prevalence ranged from 5.8% to 19.1% (mean 10.7%) in the different regions. Mean urban and rural rates were 6.6% and 15.3%, respectively (P = 0.0001). Rural mud hut dwellers, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 7 publications
0
18
1
Order By: Relevance
“…In Gabon, one study found a higher prevalence of HEV of about 2.0 times in urban (13.5%) compared with rural areas (6.4%) [73]. On the other hand, in South Africa, HEV seroprevalence is higher in rural compared with urban residents (15.3% vs. 6.6%) [98]. The difference in seroprevalence between rural and urban residents is also observed in Egypt with seroprevalence being higher in rural areas [53].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Gabon, one study found a higher prevalence of HEV of about 2.0 times in urban (13.5%) compared with rural areas (6.4%) [73]. On the other hand, in South Africa, HEV seroprevalence is higher in rural compared with urban residents (15.3% vs. 6.6%) [98]. The difference in seroprevalence between rural and urban residents is also observed in Egypt with seroprevalence being higher in rural areas [53].…”
Section: Resultsmentioning
confidence: 99%
“…Second, studies measure the prevalence of HEV infection in dissimilar subpopulations making it difficult to compare seroprevalence. For example, it is difficult to conclude whether the overall seroprevalence of HEV infection in South Africa is higher than that in Morocco when examining studies that show seroprevalence among South Africans with a mean age of 42 years is 10.7% [98] and that among younger population in Morocco is 2.2-6.8% [84,85]. Third, studies use different criteria to define acute hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis E was not routinely screened for, owing to the unavailability of a testing kit for a significant portion of the study. Historic seroprevalence data from urban and rural blacks in South Africa documented an anti–hepatitis E virus seroprevalence of 6.6% and 15.3%, respectively . With new seroprevalence data awaited, the influence hepatitis E may have had on causality assessment for DILI is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…HEV transmission, both sporadic and epidemic, is common in Africa having been identified in Egypt [8], Djibouti [7], Sudan [16], Kenya [18], Ethiopia [27], Somalia [4], South Africa [28], Algeria and Chad [29] and Morocco and Tunisia [5]. HEV is transmitted mainly be the fecal-oral route and large epidemics due to this virus have been associated with contaminated water.…”
Section: Introductionmentioning
confidence: 99%